2021
DOI: 10.3390/molecules26082161
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Decursin and Angelica gigas Nakai Root Extract in Gerbil Brain after Transient Ischemia via Protecting BBB Leakage and Astrocyte Endfeet Damage

Abstract: Angelica gigas Nakai root contains decursin which exerts beneficial properties such as anti-amnesic and anti-inflammatory activities. Until now, however, the neuroprotective effects of decursin against transient ischemic injury in the forebrain have been insufficiently investigated. Here, we revealed that post-treatment with decursin and the root extract saved pyramidal neurons in the hippocampus following transient ischemia for 5 min in gerbil forebrain. Through high-performance liquid chromatography, we defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…For reference on AEF, the AEF of astrocytes envelop almost all (>99%) of the endothelium [ 64 ]. It has been reported that, in a gerbil model of tFI, microvessels enclosed by AEF are significantly reduced in the hippocampal CA1 region after 5-min tFI [ 65 ]. Taken together, our findings suggest that the increase in GFAP immunoreactivity in astrocytes in the ischemic striatum is related with an uptake of harmful substances following tFI injury and that this astrogliosis is attenuated or protected by PTE, which may be associated with neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…For reference on AEF, the AEF of astrocytes envelop almost all (>99%) of the endothelium [ 64 ]. It has been reported that, in a gerbil model of tFI, microvessels enclosed by AEF are significantly reduced in the hippocampal CA1 region after 5-min tFI [ 65 ]. Taken together, our findings suggest that the increase in GFAP immunoreactivity in astrocytes in the ischemic striatum is related with an uptake of harmful substances following tFI injury and that this astrogliosis is attenuated or protected by PTE, which may be associated with neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…TFI was induced in accordance with a previously published method [ 4 , 12 ]. In brief, the gerbils were anesthetized by inhaling 2.5% isoflurane (Hana Pharm.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate short term memory following TFI, PAT was conducted in the light of previous studies [ 12 , 22 ]. In short, we used the Gemini Avoidance System (GEM 392) (San Diego Instruments, San Diego, CA, USA) which consists of dark and light sections communicating by a vertical sliding door between the two sections.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations